The Investigation of the Risk of Malignancy in the IntraductalPapillary Mucinous Neoplasm of the Pancreas - Koc, Mustafa (My University, 2020)
Objective: This study aims to investigate the risk of malignancy in the intraductal papillary mucinous neoplasm (IPMN) of the pancreas. Materials and Methods: Between January 2015 and February 2020, a total of 42 patients who were diagnosed as IPMN radiologically were included in the study. The radiological and clinical findings were retrospectively analyzed. Magnetic Resonance Imaging (MRI), MR Cholangiopancreatography (MRCP), and Multidetector Computed Tomography (MDCT) findings were investigated. Results: 15 of the patients were female (36%) and 27 were male (64%). The mean age was 67 (range: 45 to 81 years). (45-81). 18 cases (67%) with main duct type IPMN, 13 cases (31%) with minor duct IPMN and 11 cases (26 %) with mixed type were evaluated. In malignant cases; 3 cases (23%) diagnosed with minor branch IPMN, the mural nodule was observed. The main ductdiameter was measured ?10 mm in 10 cases (24 %). The mean cyst diameter was 12 mm (3-22 mm). The amylase level was high in all cases. Increased serum carcinoembryonic antigen (CEA) was present in 7 patients (17%) also serum carbohydrate antigen (CA 19.9) in 9 patients (21%). Positive cytology was observed in 7 cases in terms of malignancy.Conclusion: Histological features of IPMNs range from benign adenoma to malignant invasive carcinoma. It is beneficial to predict malignant lesions, to plan before surgery. Increased pancreatic main duct dilation, increased CA 19.9 level and serum CEA, presence of enhanced mural nodule and large cyst diameter are risk factors for malignancy.
Keywords: Genel ve Dahili Tıp; Patoloji; Cerrahi